Pengaruh Pemberian Afirmasi Positif (self hypnosis) Terhadap Impulsive Buying Pada Pengguna E-commerce Dewasa Awal Di Sumatera Barat - Nazir, Miftah Hayati; Ningsih, Yuninda Tria (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
The purpose of this study was to determine the effect of giving positive affirmations (self hypnosis) on impulsive buying of early adult e-commerce users in West Sumatra. The type of research used in this study is experimental research with a pre-experimenal research design with a one group pretest-posttest type. The population in this study are early adult e-commerce users who have done impulsive buying and live in West Sumatra. The number of subjects in this study were 8 people. In collecting data using the Impulsive Buying Tendency scale by Verplanken and Herabadi (2003) with a reliability value of .90. The data analysis technique used is the Wilcoxon Matched-Pairs Signed Ranks Test. A significant value of .012 <.05 was found, which means Ha is accepted. So, it can be concluded that there is an effect of giving positive affirmations (self hypnosis) on impulsive buying of early adult e-commerce users in West Sumatra.